Evaluating Economic Success Happiness, Health, and Basic Human Needs - Joffe, Michael; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
(3z(BEconomics aims to be the study of making people$1 (Bs lives better, but the focus has for too long been too narrow. This book makes a compelling case for measures of economic progress that go beyond GDP growth to put human wellbeing firmly in the spotlight, setting out a new system for assessing success.(3y (B-- Dame Diane Coyle, Bennett Professor of Public Policy, University of Cambridge, UK (3z(BMichael Joffe$1 (Bs book complements the growing criticisms to GDP as the sole (or main) metric to measure economic success with new outcome indicators that measure attainment of human needs and well-being. From this point of view, it is not only a step forward in the direction of overcoming the old and counterproductive economic metrics, but it puts forward a practical, actionable approach to measuring economic (3z(Bgrowth(3y (Bin a completely different way. I hope this book will have the reception it deserves, as a clear theoretical essay and a source of concrete and novel metrics for economics based on human needs(3y(B. -- Paolo Vineis, Professor of Environmental Epidemiology, MRC Centre for Environment and Health, School of Public Health, Imperial College London, UK This open access book argues that a new policy approach is required in order to tackle the numerous problems the world is currently facing. The priority should be on achieving better outcomes for people, especially those facing deprivation or precariousness, by meeting their basic needs. In order to achieve this, the book develops a monitoring system that can act as an objective, an incentive, and a criterion of success for policy makers at all levels of government and in civil society, as well as providing information to guide specific actions. In doing so, the book aims to promote good health and positive social functioning by providing a new approach to help assess how well basic human needs are being met. This involves monitoring the outcomes of the economy that ought to satisfy these needs. It will appeal to all those interested in public policy, official statistics and monitoring, public health and wellbeing, as well as practitioners. Michael Joffe is affiliated with the Department of Epidemiology and Biostatistics, Imperial College London, UK. He writes on topics in economics. .s
1. A successful economy is one that meets basic human needs -- 2. How to monitor an economy$1 (Bs contribution to meeting basic needs -- 3. An outline of the existing monitoring system -- 4. The proposed new monitoring system in use -- 5. Technical appendix: quantifying the impact of economic outcomes.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Political planning; Medical economics; Public health; Public Policy; Health Economics; Public Health